The Correlation between Helicobacter pylori Immunoglobulin G Seropositivity and Plasma Homocysteine Levels in Adults - Huang, Jinke; Yang, Xuefei; Zhang, Jiaqi; Wang, Fengyun; Tang, Xudong (Mediators of Inflammation, 2023)
Objectives. Helicobacter pylori (H. pylori) immunoglobulin G (IgG) seropositivity is prevalent, but its correlation with homocysteine (Hcy), a biomarker of vascular risk events, is unclear. This study is aimed at exploring the correlation of H. pylori IgG seropositivity and plasma Hcy levels in adults. Methods. Data was obtained from the National Health and Nutrition Examination Survey (NHANES) cycle 1999-2000. Hcy was measured by the Abbott homocysteine assay, and H. pylori IgG was measured by enzyme-linked immunosorbent assays. The weighted multiple logistic regression analyses with adjustments for potential confounders were conducted. Subgroup analyses stratified by gender, age, and race were performed. Results. A total of 4029 subjects aged 20-85 years were included. Population prevalence of H. pylori IgG seropositivity was 44.7% in the overall population with higher prevalence found in those with older age, Mexican Americans, lower education, and lower household income. Levels of plasma Hcy were not elevated in those with H. pylori IgG seropositivity versus seronegativity (β -0.120 (-0.438, 0.199) P=0.462). This difference was not significant after stratifying by gender and age. However, in the subgroup analyses stratified by race, a negative correlation between H. pylori seropositivity and plasma Hcy levels was observed in Mexican Americans (β -0.802 (-1.253, -0.352) P<0.001). Conclusions. H. pylori IgG seropositivity was not associated with plasma Hcy levels in the general population, but there may be a negative correlation in Mexican Americans. These findings provide new insights to advance the research of the link between plasma Hcy levels and stomach health.